Legal Review of the Validity of the Use of Smart Contracts in Business Transactions in Indonesia and Its Regulation in Various Countries - Muhammad Ilman Abidin (Universitas Negeri Semarang, 2023)
The increasingly massive use of the internet is now affecting the economic world which is characterized by the birth of E-Commerce. E-Commerce mechanism that does not brings together sellers and buyers directly, this raises a variety of problems on the subjective and objective terms of the sale and purchase agreement. Smart Contracts are actually different from conventional contracts written on paper. They are also different from electronic contracts. A clause in the agreement, which takes the form of programming code, requires blockchain as a distributed storage technology, which sets them apart. In addition, Smart Contracts serve to execute contracts automatically. Therefore, the article aims to analyze the advantages of Smart Contracts compared to conventional contracts and how the validity of using smart contracts in Indonesian law, and why business transactions in Indonesia should start using smart contracts. The result obtained is that the use of Smart Contracts are completely automated and rely on software logic, making them transparent and visible to all parties involved. The use of Smart Contract in buying and selling transactions is considered very important considering the advantages in terms of security, verification, changes in the contents of the agreement, and evidentiary power. As for Indonesian law, the use of Smart Contracts is permissible as long as it does not violate the validity of the agreement as stated in the Civil Code. The use of Smart Contracts offer several advantages over traditional contracts, including trasparency, autonomy, speed, accuracy, security, and savings.